Notes on Manota Williston (Diptera: Mycetophilidae) from Australia and Papua New Guinea, with description of two new species - Kurina, Olavi; Hippa, Heikki; Amorim, Dalton De Souza (Zootaxa, 2019)
Two new species, Manota williamsi sp. n. and Manota kerri sp. n., are described from Australia and Papua New Guinea, respectively. The former represents the second Manota species recorded from continental Australia. Characterised by setose anepisternum and non-setose laterotergite, M. williamsi is similar to M. gemella Hippa, 2007, but the presence of the mid tibial organ would group it together with five species from New Zealand. Manota kerri resembles M. alulata Kurina & Hippa, 2015 in having a bilobed gonostylus and sternite 9 entirely fused with the gonocoxa, but differs by other details of the hypopygium. New records of M. subspathula Hippa, 2007 from Australia and Papua New Guinea, and M. biungulata Hippa, 2007, M. evexa Hippa 2007, M. hamulata Colless, 1966, M. perissochaeta Hippa, 2007 and M. serawei Hippa, 2007 from Papua New Guinea are presented.